2012
DOI: 10.1007/978-3-642-32009-5_28
|View full text |Cite
|
Sign up to set email alerts
|

Crowd-Blending Privacy

Abstract: Abstract.We introduce a new definition of privacy called crowdblending privacy that strictly relaxes the notion of differential privacy. Roughly speaking, k-crowd blending private sanitization of a database requires that each individual i in the database "blends" with k other individuals j in the database, in the sense that the output of the sanitizer is "indistinguishable" if i's data is replaced by j's.We demonstrate crowd-blending private mechanisms for histograms and for releasing synthetic data points, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 21 publications
2
77
0
Order By: Relevance
“…Due to its inability of achieving practical implementation, there is a surge of works nowadays that tend to combine the practicalness of syntactic approaches with the effectiveness of DP. Since BangA performs very efficient multidimensional partitioning to achieve high quality generalization, inspired by Gehrke et al [26] DP relaxation, as a future work, we may adopt the following framework for achieving DP:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its inability of achieving practical implementation, there is a surge of works nowadays that tend to combine the practicalness of syntactic approaches with the effectiveness of DP. Since BangA performs very efficient multidimensional partitioning to achieve high quality generalization, inspired by Gehrke et al [26] DP relaxation, as a future work, we may adopt the following framework for achieving DP:…”
Section: Discussionmentioning
confidence: 99%
“…Quite recently, there is an encouraging trend of combining DP style privacy with generalization based approaches. Specifically, the works in [25][26][27] provide interesting directions to achieve DP for k-anonymity based generalization approaches since Differentially Private k-anonymous release has an effective privacy vs. utility trade-off.…”
Section: Synopsismentioning
confidence: 99%
“…Works on Differential-Privacy under Sampling [13], Crowd-Blending Privacy [8], Coupled-Worlds Privacy [2] or Outlier Privacy [15] have shown that if sufficiently many users are indistinguishable by a mechanism, and this mechanism operates on a dataset obtained through a robust sampling procedure, differential privacy can be satisfied with only little data perturbation. Our work differs in that we make no assumptions on the indistinguishability of different entities, and that our aim is to guarantee membership privacy rather than differential privacy.…”
Section: Relation To Prior Workmentioning
confidence: 99%
“…Previous works mainly focus on the unbounded-DP case, and thus are not directly applicable to situations where the size of the dataset is public. Furthermore, previously considered adversarial priors are either uniform [13,2] or only allow for a fixed number of known entities [8,15]. Finally, very few results are known on how to design general mechanisms satisfying distributional variants of DP.…”
Section: Relation To Prior Workmentioning
confidence: 99%
See 1 more Smart Citation